Amsterdam koopt kunst : Gemeentelijke Kunstaankopen 1981-1982. (Amsterdam : Museum Fodor, 1983)
Abramovic, Marina & Ulay ; Andreas-Tüzüner, Isik ; Andriesse, Erik ; Appenzeller, Hans ; Baart, Theo ; Baren, Peter ; Bastiaans, Christiaan ; van den Berg, Henk ; Berghuis, Jaap ; Biem, Walthère ; Bien, Ania ; Blits, Mieke ; Blom, Ansuya ; van den Boom, Herman ; Brants, Pauline ; van den Brink, Mecky ; Broecke, Erik ten ; Broek, René Van Den ; de Bruin, Jan ; de Bueger, Chris ; Buisman, Sjoerd ; Buytendijk, Antonie F.J. ; Cardena, Michel ; Carelse, Renate ; Compier, Wim ; Content, Eli ; Cuypers, Mathilde ; Derrez, Paul ; Dibbets, Jan ; Dijkman, Annelies ; van Dorst, Jacques ; van Egmond, Hans ; van Elden, Willem ; van Elk, Ger ; van Fastenhout, Geert ; Franssens, Jean-Paul ; Freijmuth, Alphons ; Fridfinnsson, Hreinn ; van Genderen, Agnes ; Gerrets, Boris ; Gibbs, Michael ; de Goede, Kees ; Gordon, Maya ; Greefkens, Leonie ; Grinberg, Buky ; Groenendijk, Mitsy ; Haak, Jan ; de Haas, Laetitia ; Hahn, Susanne ; van Haren, Elma ; Heemskerk, Cees ; Heiden, Cécile Van Der ; Hetterscheid, Otto ; van den Heuvel, Guusje ; Heyboer, Anton ; van der Heyden, Peter ; Hijstek, Antoinette ; Hillenius, Jaap ; Hofstra, Sjoerd ; Holstein, Pieter ; Honing, Willem ; Hoover, Nan ; Hooykaas & Stansfield ; Horonyová, Dana ; Horst, Els ter ; Huismans, Sipke ; Julia, Olivier ; Kamermans, Klaartje ; Kessler, Beppe ; King, Tjoe Fang ; Klein, Aart ; Koenigs, Christine ; van Koningsbruggen, Rob ; Kraft, Bea ; Kronenberg, Marianne ; Kruit, Baukje ; Kuipers, Paul ; Lamberts, Aart ; Lap, Geert ; Lataster, Ger ; Levav, Ruven ; Lewkowicz, Stanislaw ; Liggins, John ; van Lith, Nel ; Lodeizen, Frank ; Loeb, Jeanette ; Lucassen ; Luik, Hieke ; Makkink, Cornelis ; Makkink, Herman ; Marks, Charles ; Martin, Lous ; Van Meerwijck, Hans ; Meijers, Karel ; Menken, Richard ; Müller, Dirk ; etc.
biog., tent. per kunstenaar
Amsterdam koopt kunst : Gemeentelijke Kunstaankopen 1981-1982, Museum Fodor, Amsterdam, 05.02.1983 - 06.03.1983
Nederlands & Engels
boek
Keywords: Amsterdam